PERBAIKAN TATA LETAK IKM VULKANISIR BAN GUNUNG TIMUR DI KOTA DUMAI - Ferdiansyah; Fitra; Habibur Rohman; M.Fathir N.A (Jurnal Mitra Teknik Industri, 2025)
Gunung Timur Tire Retreading SME, located in West Dumai District, Dumai City, is experiencing inefficiencies in its facility layout. These inefficiencies result in irregular workflows, longer material handling distances, and suboptimal space utilization, which directly affect operational efficiency and productivity. This study aims to improve the facility layout to enhance workflow efficiency through the application of the Systematic Layout Planning (SLP) method and a graph-based approach. The research process includes field data collection, preparation of the operation process chart, from-to chart, activity relationship chart, relationship diagram, space requirement calculation, as well as the design and evaluation of alternative layouts. The analysis results show that the proposed layout using the SLP method reduced the total material handling distance from 545.71 meters to 346.8 meters, while the layout using the graph-based method resulted in a distance of 391.3 meters. The layout proposed using the SLP method demonstrated the highest efficiency, achieving a 36.45% reduction in material handling distance, improved workflow organization, and more optimal space utilization. Eventually, the implementation of the SLP method offers a strategic solution to improve the operational efficiency and productivity of the tire retreading IKM.